Finance and Development, December 1972. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1972)
This paper describes what the limits to growth are. The paper highlights that many critical variables in global society-particularly population and industrial production-have been growing at a constant percentage rate so that, by now, the absolute increase each year is extremely large. Such increases will become increasingly unmanageable unless deliberate action is taken to prevent such exponential growth. The paper also underscores that physical resources-particularly cultivable land and nonrenewable minerals-and the earth's capacity to 'absorb' pollution are finite.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet